Lung Cancer Screening Participation: Developing a Conceptual Model to Guide Research - Carter-Harris, Lisa (Res Theory Nurs Pract, 2016)
PURPOSE: To describe the development of a conceptual model to guide research focused on lung cancer screening participation from the perspective of the individual in the decision-making process. METHODS: Based on a comprehensive review of empirical and theoretical literature, a conceptual model was developed linking key psychological variables (stigma, medical mistrust, fatalism, worry, and fear) to the health belief model and precaution adoption process model. RESULTS: Proposed model concepts have been examined in prior research of either lung or other cancer screening behavior. To date, a few studies have explored a limited number of variables that influence screening behavior in lung cancer specifically. Therefore, relationships among concepts in the model have been proposed and future research directions presented. CONCLUSION: This proposed model is an initial step to support theoretically based research. As lung cancer screening becomes more widely implemented, it is critical to theoretically guide research to understand variables that may be associated with lung cancer screening participation. Findings from future research guided by the proposed conceptual model can be used to refine the model and inform tailored intervention development.